Establishment and Characterization of Japanese Encephalitis Virus-Specific, Human CD4(+) T-Cell Clones: Flavivirus Cross-Reactivity, Protein Recognition, and Cytotoxic Activity - Aihara, Hirokuni (American Society for Microbiology, 1998)
We analyzed the CD4(+) T-lymphocyte responses of two donors who had received Japanese encephalitis virus (JEV) vaccine 6 or 12 months earlier. Bulk culture proliferation assays showed that peripheral blood mononuclear cells (PBMC) responded to JEV antigens (Ag) but also responded at lower levels to West Nile virus (WNV) and dengue virus type 1, 2, and 4 (D1V, D2V, and D4V, respectively) Ag. Five JEV-specific CD4(+) human T-cell clones and one subclone were established from PBMC of these two donors. Two clones responded to WNV Ag as well as to JEV Ag, whereas the others responded only to JEV Ag. Three of five CD4(+) T-cell clones had JEV-specific cytotoxic activity and recognized E protein. The HLA restriction of the JEV-specific T-cell clones was examined. Three clones were HLA-DR4 restricted, one was HLA-DQ3 restricted, and the HLA restriction of one clone was not determined. T-cell receptor analysis showed that these clones expressed different T-cell receptors, suggesting that they originated from different T lymphocytes. These results indicate that JEV vaccine induces JEV-specific and flavivirus-cross-reactive CD4(+) T lymphocytes and that these T lymphocytes recognize E protein. The functions and HLA restriction patterns of these T lymphocytes are, however, heterogeneous.